2017
DOI: 10.1007/s00701-017-3432-5
|View full text |Cite
|
Sign up to set email alerts
|

Borders of STN determined by MRI versus the electrophysiological STN. A comparison using intraoperative CT

Abstract: BackgroundIt is unclear which magnetic resonance imaging (MRI) sequence most accurately corresponds with the electrophysiological subthalamic nucleus (STN) obtained during microelectrode recording (MER, MER-STN). CT/MRI fusion allows for comparison between MER-STN and the STN visualized on preoperative MRI (MRI-STN).ObjectiveTo compare dorsal and ventral STN borders as seen on 3-Tesla T2-weighted (T2) and susceptibility weighted images (SWI) with electrophysiological STN borders in deep brain stimulation (DBS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…One study showed that the final stimulation site, based on MER and intraoperative stimulation, was located more lateral and superior than both atlas and MRI based targets . Also, newer studies show discrepancies comparing borders on T2 and SWI MRI sequences compared to the electrophysiological STN . Further research is needed to evaluate the impact of these newer techniques on target accuracy and clinical outcome …”
Section: Discussionmentioning
confidence: 99%
“…One study showed that the final stimulation site, based on MER and intraoperative stimulation, was located more lateral and superior than both atlas and MRI based targets . Also, newer studies show discrepancies comparing borders on T2 and SWI MRI sequences compared to the electrophysiological STN . Further research is needed to evaluate the impact of these newer techniques on target accuracy and clinical outcome …”
Section: Discussionmentioning
confidence: 99%
“…Improvements can refer to a smaller deviation between planned and actual lead location, a reduction in reimplantation or removal requirements, increased clinical efficacy, or decrease in associated side effects. However, the use of T2* contrasts and UHF-MRI remains widely debated and requires further validation [ 37 , 70 , 144 , 148 , 149 , 150 ].…”
Section: Sequence Types and Contrastsmentioning
confidence: 99%
“…Clinical T2w images often incorporate anisotropic voxel sizes with large slice thickness in the z direction. This allows for higher in-plane resolution along the axial plane, which is primarily used for targeting ( Figure 3 ) [ 145 , 149 ]. Voxel sizes will typically range between 0.45 × 0.45 × 2 mm and 1 × 1 × 3 mm.…”
Section: Voxel Sizesmentioning
confidence: 99%
“…However, clinical outcome after STN DBS varies widely between patients [2][3][4][5]. In part, this may be explained by individual anatomical variability of the STN combined with poor visualization of the dorsolateral sensorimotor part of the STN with current imaging techniques [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…As susceptibility-weighted imaging (SWI) gained interest in DBS surgery for PD due to its better visualization of the STN compared to T2-weighted imaging, discrepancies between T2-weighted imaging and SWI have been a subject of study [6,7,15,16]. In localizing the medial STN border, the correspondence between T2-weighted imaging and SWI remains unclear.…”
Section: Introductionmentioning
confidence: 99%